2015
DOI: 10.17645/si.v3i1.125
|View full text |Cite
|
Sign up to set email alerts
|

Modeling for Determinants of Human Trafficking: An Empirical Analysis

Abstract: This study aims to identify robust push and pull factors of human trafficking. I test for the robustness of 70 push and 63 pull factors suggested in the literature. In doing so, I employ an extreme bound analysis, running more than two million regressions with all possible combinations of variables for up to 153 countries during the period of 1995-2010. My results show that crime prevalence robustly explains human trafficking both in destination and origin countries. Income level also has a robust impact, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 26 publications
(37 reference statements)
4
60
0
9
Order By: Relevance
“…If the relationship with the smuggler ends once the person reaches their destination this is considered human smuggling; however, if the smuggler entraps the person in the destination country and forces them into labor, prostitution, or other atrocities, this is considered human trafficking (Bales et al, 2009). Cho (2015) states human trafficking research is still in its infancy; however, the body of literature exploring the root causes and drivers of human trafficking is growing. The literature has broadly categorized these factors as supply side, or "push" factors, demand side or "pull" factors and as facilitating factors.…”
Section: Overview Of Human Traffickingmentioning
confidence: 99%
See 4 more Smart Citations
“…If the relationship with the smuggler ends once the person reaches their destination this is considered human smuggling; however, if the smuggler entraps the person in the destination country and forces them into labor, prostitution, or other atrocities, this is considered human trafficking (Bales et al, 2009). Cho (2015) states human trafficking research is still in its infancy; however, the body of literature exploring the root causes and drivers of human trafficking is growing. The literature has broadly categorized these factors as supply side, or "push" factors, demand side or "pull" factors and as facilitating factors.…”
Section: Overview Of Human Traffickingmentioning
confidence: 99%
“…The literature has broadly categorized these factors as supply side, or "push" factors, demand side or "pull" factors and as facilitating factors. In regards to the push or supply factors, past research has found countries that suffer from poverty, crime, corruption, unstable institutions, and/or are plagued with conflict and upheaval tend to be the greatest source of human trafficking victims (Agbu, 2003;Bales, 2007;Cho, 2015;Rao & Presenti, 2012;Surtees, 2008). These countries are often referred to as "origin" countries as individuals seek to migrate out of these areas in search of a better life and in the process fall victim to human traffickers.…”
Section: Overview Of Human Traffickingmentioning
confidence: 99%
See 3 more Smart Citations